Inflammatory myopathy and interstitial lung disease in antisynthetase syndrome with PL-7 antibody - Aguiar Rosa, Sílvia (BMJ Publishing Group, 2014)
We report a case of a 72-year-old Caucasian woman with PL-7 positive antisynthetase syndrome. Clinical presentation included interstitial lung disease, myositis, ‘mechanic's hands’ and dysphagia. As lung injury was the main concern, treatment consisted of prednisolone and cyclophosphamide. Complete remission with reversal of pulmonary damage was achieved, as reported by CT scan, pulmonary function tests and functional status.